2000
DOI: 10.1038/sj.gt.3301202
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Flt-1 gene therapy for peritoneal metastases using HVJ-cationic liposomes

Abstract: Many studies have reported a close association between VEGF and tumor angiogenesis. The aim of the present study was to evaluate the effectiveness of gene therapy against cancer, including peritoneal metastasis, using a cDNA encoding a soluble type of Flt-1, one of the VEGF receptors. In a peritoneal metastasis model of MKN45 human gastric cancer cells, mice repetitively treated with intraperitoneal injections of HVJ-Fex, a type of HVJ-cationic liposome encapsulating a plasmid expressing soluble mFlt-1, exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 35 publications
(36 reference statements)
0
35
0
Order By: Relevance
“…[11][12][13][14] In these studies, gene delivery with either Flk-1 or Flt-1 elicited a B80% suppression in tumor growth that was associated with decreased tumor microvessel density. 11 Similar antiangiogenic properties were demonstrated in the corneal micropocket assay in which Flk-1 and Flt-1 strongly inhibited corneal neovascularization.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[11][12][13][14] In these studies, gene delivery with either Flk-1 or Flt-1 elicited a B80% suppression in tumor growth that was associated with decreased tumor microvessel density. 11 Similar antiangiogenic properties were demonstrated in the corneal micropocket assay in which Flk-1 and Flt-1 strongly inhibited corneal neovascularization.…”
Section: Discussionmentioning
confidence: 91%
“…Gene transfer with sFlt-1 or sFlk-1 markedly reduced tumor growth by inhibiting tumor angiogenesis in various animal tumor models. [11][12][13][14][15] Furthermore, in corneal micropocket assays in rodents, gene delivery significantly attenuated neovascularization induced by sustained release VEGF pellets. 11,16 Wound healing is a complex, dynamic process in which angiogenesis has been hypothesized to play an integral part since the formation of new blood vessels is a necessary step that allows a variety of mediators and regulators to reach the center of the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with sFlt-1, a naturally-occurring truncated and secreted form of VEGF receptor Flt-1, has been shown to inhibit angiogenesis in a variety of disease models. 29,30,35 The anti-angiogenic action of sFlt-1 is due to its ability to directly sequester VEGF and to form heterodimers with membrane-bound Flt-1 and VEGF receptor 2. 28,36 It is widely believed that VEGF up-regulation also plays a major part in the development of ocular NV.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality associated with gastric cancer has remained relatively stable over the past 20 years, suggesting that new therapies to combat this problem are urgently needed (Karpeh et al, 2001). Recent studies have shown that targeting the tumour vasculature may be of therapeutic benefit in gastric cancer (Mori et al, 2000;Yoshikawa et al, 2000;Jung et al, 2002;Kamiyama et al, 2002).…”
mentioning
confidence: 99%